2019
DOI: 10.1007/s12031-019-01411-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Multiple Reaction Monitoring Analysis of CSF Identifies UCHL1 and GPNMB as Candidate Biomarkers for ALS

Abstract: The neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and Parkinson’s disease (PD) share some common molecular deficits including disruption of protein homeostasis leading to disease-specific protein aggregation. While insoluble protein aggregates are the defining pathological confirmation of diagnosis, patient stratification based on early molecular etiologies may identify distinct subgroups within a clinical diagnosis that would respond differently in therapeutic development programs. We are dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 63 publications
(73 reference statements)
5
26
0
Order By: Relevance
“…Our results indicated that CSF UCHL1 is a promising biomarker for ALS diagnosis, consistent with some previous studies 14,16 . Specifically, we found significantly elevated CSF UCHL1 in both discovery and validation cohorts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicated that CSF UCHL1 is a promising biomarker for ALS diagnosis, consistent with some previous studies 14,16 . Specifically, we found significantly elevated CSF UCHL1 in both discovery and validation cohorts.…”
Section: Discussionsupporting
confidence: 92%
“…Summarily, we selected a panel of candidate neurodegenerative biomarkers, based on our previous research and other published studies. These included Glial fibrillary acidic protein (GFAP), 8,9 DJ1, 10 S100B, 9,11 Amyloid beta 40 (Abeta 40), Amyloid beta 42 (Abeta 42), 9 Transglutaminase 2 (TGM2), 12 α‐synulein, 13 Ubiquitin C‐terminal hydrolase L1 (UCHL1), 14 and Neuron specific enolase (NSE) 15 . We recruited a discovery cohort, comprising 20 ALS patients and 20 patients with other neurological diseases, and screened it for possible biomarkers using the Luminex platform.…”
Section: Introductionmentioning
confidence: 99%
“…UCHL1 is a ubiquitin-protein hydrolase important for protein homeostasis that is expressed in neurons and neuroendocrine cells, whereas APOB is associated with metabolic changes in ALS [30,35]. Consistent with previous studies, we found that all of these candidate proteins were elevated in CSF samples from patients with ALS [17,22,23,[36][37][38][39]. This observation independently strengthens the potential of these proteins as reliable biomarkers for ALS, and importantly, validates our approach as a method to identify novel candidate biomarkers.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to the classical fluid-based biomarkers of neurodegeneration such as Aβ 42 and Tau, markers of neuronal health and astrogliosis such as Ubiquitin C-Terminal hydroxylase (UCH-L1) and glial fibrillary acidic protein (GFAP) are also seen to be increased in neurodegenerative disorders such as Alzheimer’s disease, ALS, and frontotemporal dementia [ 45 , 46 , 47 , 48 ]. Our data show that a subset of these markers is also elevated in CSF of nMPS II patients relative to the control group.…”
Section: Resultsmentioning
confidence: 99%